Pengendalian Kualitas pada Produksi Cable Protector: Studi Kasus PT Schlemmer Automotive Indonesia - Prismawinda Anifanindi; Dwi Irwati (DPPM Universitas Pelita Bangsa, 2022)
Quality control and handling of abnormalities is one of the important aspects to maintain the capability of the production process and keep the total defective products produced not exceeding 3300 ppm as a commitment of PT Schlemmer Automotive Indonesia in carrying out its production. An important benefit in the study of quality control and abnormality handling is to be able to learn how quality control measures are carried out and to study the root causes of problems that arise during the production process. Quality control is carried out using QC Seven Tools statistical tools in the form of checksheets, Pareto diagrams, cause-and-effect diagrams and why-why analysis. There are several anomalies that occur on the production floor. Among them are defects in the hinge. This hinge crack defect produces 109 ppm which has a major contribution to the occurrence of quality anomalies. From the analysis of the cause of the hinge crack, there are 3 material flows supplied by 3 different gates. The result of this study is that the highest defect was found in the 7278-9830-3W part with a hinge crack defect of 109 ppm. This is due to the presence of the meeting of the material in the hinge area, causing the material at the hinge to be inhomogeneous. Keywords: Pareto Diagram, QC Seven Tools, Why-Why Analysis